Inductance simulation using GaAs MESFETs - Tangsrirat, Worapong; Surakampontorn, Wanlop; Riewruja, Vanchai; Dumawipata, Teerasilapa (My University, 1998)
This paper proposes a method for an inductance simulation by using GaAs MESFET (Gallium Arsenide MEtal Semiconductor Field-Effect Transistor) devices. The realization method is based on the use of a GaAs voltage-to-current transducer and is also suitable for implementing in monolithic integrated circuit form. The circuit has wide bandwidth, good linearity and the simulated inductive reactance value is a linear function of resistor and capacitor. The PSPICE simulation results show that the properties of the circuit are in close agreement with the theoretical prediction.